(untitled) (Al-Qamar, 2023)
Fawā’id al-Fuwād is a renowned book written by Nizamuddīn Auwliya. The book offers a collection of valuable insights and teachings from Nizāmuddīn Auwliyā, a renowned medieval Sufi saint of the Chishtī order in India. This book contains valuable insights into the spiritual journey of a Sufi and highlights the virtues, wisdom, and guidance necessary for achieving true love and devotion to God. It is believed that Hazrat Nizāmuddīn Auwliyā wrote this book to convey his message to his followers who were unable to meet him in person. The book is considered a masterpiece of Sufi literature and has been translated into several languages. Through Fawā’id al-Fuwād, readers gain a deeper understanding of Sufism and its teachings, making it a valuable resource for those pursuing the path of spirituality. This is an analytical study to explore the methodology style of Fawā’id al-Fuwād and its contemporary importance. For this purpose, data is gathered from secondary sources; books, articles and online sources. The study reveals that Fawā’id al-Fuwād is the first book of al-Malfūzāt that was first compiled in book form. Its position is also high in the sense that it contains the most Hadiths with text. The book is a source and source book of spiritual teachings. This book not only emphasized on worship but also enlightened people’s hearts with Islamic teachings. It Encourages people to have a good character through the morals of the Prophet (PBUH) in Fawā’id al-Fuwād.